(untitled) (Hekima Review, 2022)
Seeking God in cosmic evolution requires closer exchanges between science, philosophy and theology. The material and the spiritual in the process of evolution cannot be separated. As the latest and most spiritually conscious emergent forms of life in cosmic evolution, humans play an indispensable role as co-creators in moving the process of evolution forward into the future. While science needs to avoid the pitfalls of scientism, philosophy needs to avoid an excessive and exclusive emphasis on rationalism. Theology, for its part, can help to supply an ultimate explanation for the emerging dimensions in scientific discoveries through the immanence of the Word of God and the Spirit of God in ongoing creation. There appear to be fixed patterns or structures that emerge both on the macrocosmic inanimate level as well as on the microcosmic animate level which reveal almost inevitable convergences in addition to inherent attractive forces enabling entities to transcend themselves. Matter matters supremely in the cosmic process but, unless enlivened by spirit, it is dead. Specific attention is drawn to the concepts such as information, relationships, creativity, attractors and possibilities. Scientific discoveries can be seen to be consonant with theological beliefs as partial analogous reflections of the presence and activity of the Triune God in the evolutionary process. The whole of creation is seen to be drawn to its completion in the alluring love of the Creator. The need for a stronger interface between science, philosophy and theology is emphasized in helping to understand the process of evolution.